"COVID knocked me straight into the dirt": perspectives from people experiencing homelessness on the impacts of the COVID-19 pandemic - Natalia M. Rodriguez; Rebecca G. Martinez; Rebecca Ziolkowski; Cealia Tolliver; Hope Young; Yumary Ruiz (BMC, 2022)
Abstract Background People experiencing homelessness are uniquely susceptible and disproportionately affected by the impacts of the COVID-19 pandemic. Understanding context-specific challenges, responses, and perspectives of people experiencing homelessness is essential to improving pandemic response and mitigating the long-term consequences of the pandemic on this vulnerable population. Methods As part of an ongoing community-based participatory research study in partnership with a homeless service organization in Indiana, semi-structured interviews were conducted with a total of 34 individuals experiencing homelessness between January and July 2021. Guided by the NIMHD Health Disparities Research Framework, which builds on the socio-ecological model, data was thematically coded using Nvivo12 qualitative coding software and themes were organized by levels of influence (individual, interpersonal, community, societal) and domains of influence (biological, behavioral, physical/built environment, sociocultural environment, health care system). Results Narratives revealed numerous and compounding factors affecting COVID-19 risks and health outcomes among people experiencing homelessness across all levels and domains of influence. At the individual level, people experiencing homelessness face unique challenges that heightened their susceptibility to COVID-19, including pre-existing physical and mental health conditions, substance use and behavioral health risks, socioeconomic precarity, and low health literacy and COVID-related knowledge. At the interpersonal level, poor communication between people experiencing homelessness and service providers led to limited understanding of and poor compliance with COVID safety measures. At the community level, closures and service disruptions restricted access to usual spaces and resources to meet basic needs. At a policy level, people experiencing homelessness were disregarded in ways that made pandemic relief resources largely inaccessible to them. Conclusions Our findings reveal important and mitigable issues with ongoing pandemic response efforts in homeless populations through direct, first-hand accounts of their experiences during COVID-19. These insights offer opportunities for multilevel interventions to improve outreach, communication, and impact mitigation strategies for people experiencing homelessness. This study highlights the importance of centering the voices of vulnerable communities to inform future pandemic response for homeless and other underserved and marginalized populations.